How does North Macedonia’s agricultural policy support adhere to the EU CAP? - Aleksandra Martinovska Stojcheska, Ana Kotevska, Ivana Janeska Stamenkovska, Dragi Dimitrievski (Association of Agricultural Economists of Slovenia (DAES), 2022)
This paper presents the recent development of agricultural policy support in North Macedonia in the context of the EU approximation process. The applied conceptual framework focuses on the key principles of agricultural policy harmonization with the EU CAP. The Agricultural Policy Measures Classification (APMC) tool is used to obtain a detailed understanding of the structure and level of the existing support (and comparison with Western Balkan countries and the EU CAP). The results show an increasing trend in total budgetary transfers to the agricultural sector. Agricultural support is composed mostly of coupled direct payments and on-farm investment support, whereas the support for environmental and other societal benefits has minor representation. While largely committed to adhere to the CAP in future, the agricultural policy actually implemented diverges from the declared planning, reflecting domestic interests.1